2017
DOI: 10.1002/hep.29510
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of glecaprevir/pibrentasvir in Japanese patients with chronic genotype 2 hepatitis C virus infection

Abstract: Glecaprevir (nonstructural protein 3/4A protease inhibitor) and pibrentasvir (nonstructural protein 5A inhibitor) (G/P), a coformulated once‐daily, all oral, ribavirin (RBV)‐free, direct‐acting antiviral regimen, was evaluated for safety and efficacy in hepatitis C virus genotype 2 (GT2)–infected Japanese patients, including those with compensated cirrhosis. CERTAIN‐2 is a phase 3, open‐label, multicenter study assessing the safety and efficacy of G/P (300/120 mg) once daily in treatment‐naive and interferon ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
107
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 21 publications
2
107
0
Order By: Relevance
“…Theoretically, RAVs in Non‐structural protein (NS)3 and NS5A regions might influence the therapeutic efficacy of GLE/PIB in HCV GT2. However, the phase III trial of GLE/PIB for GT2 patients (CERTAIN‐2 trial) has reported that RAVs in NS3 and NS5A regions at the baseline did not affect the efficacy in either GT2a or GT2b . As the method for detecting RAVs in both NS3 and NS5A regions of HCV GT2 does not exist on a commercial basis, we could not investigate RAVs in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Theoretically, RAVs in Non‐structural protein (NS)3 and NS5A regions might influence the therapeutic efficacy of GLE/PIB in HCV GT2. However, the phase III trial of GLE/PIB for GT2 patients (CERTAIN‐2 trial) has reported that RAVs in NS3 and NS5A regions at the baseline did not affect the efficacy in either GT2a or GT2b . As the method for detecting RAVs in both NS3 and NS5A regions of HCV GT2 does not exist on a commercial basis, we could not investigate RAVs in this study.…”
Section: Discussionmentioning
confidence: 95%
“…In areas where regimens such as SOF + velpatasvir, glecaprevir/pibrentasvir, or SOF/ledipasvir are available, these regimens could be an alternative choice for HCV genotype 2 cirrhotic patients. For these patients, Japanese clinical trials have shown that the rate of SVR was 100% (18/18) for the glecaprevir/pibrentasvir regimen and 93% (13/14) for the SOF/ledipasvir regimen . The global ASTRAL‐2 study showed that the rate of SVR was 93% (40/43) by SOF + velpatasvir .…”
Section: Discussionmentioning
confidence: 99%
“…Considering the metabolism and excretion of these DAAs, it is presumed that they can be administered to patients with CKD. A phase 3 trial of glecaprevir/pibrentasvir demonstrated the high efficacy and safety in patients with CKD and those undergoing hemodialysis . IFN/ribavirin‐free, glecaprevir/pibrentasvir for pan‐genotype chronic hepatitis C patients is expected to treat genotype 2–6 chronic hepatitis C patients with CKD including hemodialysis, with high efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%